2019
DOI: 10.1038/s42004-019-0159-7
|View full text |Cite
|
Sign up to set email alerts
|

The impact of clothing on ozone and squalene ozonolysis products in indoor environments

Abstract: Multiphase reactions of ozone with human skin oils impact indoor air quality by depleting ozone and forming semi-volatile organic compounds, which can be respiratory and skin irritants. Here we demonstrate the impact of clothing on indoor air composition and human exposure by integrating indoor chemistry modeling over a wide range of different spatial and temporal scales. Constrained by molecular dynamics simulations that provide key kinetic parameters, the kinetic model reproduces experimental measurements an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
119
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(126 citation statements)
references
References 48 publications
4
119
0
Order By: Relevance
“…96 Other recent studies have shown how soiled clothing protects us from gas-phase oxidants but can also enhance dermal exposure to chemical pollutants. 141,205,250,251 Residence time, light and oxidant levels. Also different from outdoors is the short, roughly hour-long residence time of indoor air, and the lower concentrations of gas-phase oxidants and light.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…96 Other recent studies have shown how soiled clothing protects us from gas-phase oxidants but can also enhance dermal exposure to chemical pollutants. 141,205,250,251 Residence time, light and oxidant levels. Also different from outdoors is the short, roughly hour-long residence time of indoor air, and the lower concentrations of gas-phase oxidants and light.…”
Section: Discussionmentioning
confidence: 99%
“…177,187,203 Recently, aspects of this complexity have been added into models of multiphase oxidation processes occurring in the indoor environment, such as the oxidation of unsaturated lipids in skin oil and the formation of associated carbonyls 204 and in soiled clothing. 205 Ozone also reacts heterogeneously with many other electronrich substrates, such as condensed-phase polycyclic aromatic hydrocarbons (PAHs) and nicotine. [206][207][208][209][210] These pollutants can arise from incomplete combustion processes, such as candle burning, cooking stove operation, and smoking.…”
Section: (C) Multiphase Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…30,32,[52][53][54] Recent studies have focused on surface adsorption and oxidation chemistry of relevant OCs, including ozonolysis of an unsaturated triglyceride 55 and squalene. 56 Surface Chemistry of Nitrogen Oxides Including HONO Indoors It is well known that nitrogen oxides, NO and NO 2 , are present in indoor air from combustion processes, including cooking, and outdoor transport. 17 More recently, painted surfaces have been identified as a source of photochemically produced NO and NO 2 .…”
Section: Surface Oxidation Chemistry Of Organic Compounds In Indoor Ementioning
confidence: 99%
“…Based on the previous studies and recommendations regarding CFD validation process [32][33][34][35][36], we performed experiments in a full-scale environmental chamber and used the measurement data for validating the CFD model as described in the following sections. Figure 1).…”
Section: Validation Of Cfd Modelmentioning
confidence: 99%